Requirements for the possibility of applying international accounting standards on financial instruments-an applied study in the national bank of Baghdad (Raparin Journal of Humanities (RJH), 2019)
The reality today proves that growth and success have become the share of financial markets that have learned how to read the road map and achieve leadership by investing in the so-called derivatives, where the center of gravity in financial markets has shifted from relying on simple financial instruments to relying on Great for innovation and creativity to create innovative financial products that cover the needs of investors. The issue of derivatives has become an important place in global markets. The importance of this study is illustrated by the nature of the accounting treatment of these instruments and how they are disclosed in the annual financial statements of companies and banks dealing with them according to the international accounting standard No. (32) and how to recognize and measure the financial instruments, and disclose them according to the International Accounting Standard No. (7-9), in order to clarify the nature of the analysis required to determine the correct accounting processing when using these instruments, as the financial statements published by the dealers of financial instruments and provided to end users must include sufficient information about them with To clarify the risks for which the transactions were carried out, the extent to which such information is covered (is it for hedging purposes or for trading purposes), the degree of risk and how to account for it, and through this process has been concluded among the most important risks to which the bank is exposed is the risk of changing interest rates, given that the net Interest income constitutes a large percentage of the bank's returns, the interest rate risk is particularly important, as the case of high interest rates creates for banks the risk of paying higher rates on deposits for the future and other bank demands compared to what they get from their glory, and the situation is quite the opposite when the Shame interest. The study recommends that the bank dealing in derivative financial instruments distinguish between the profitability of trading in these and other investment instruments, and for the instruments used for the purposes of hedging the risk of interest rates, as well as the bank to clarify the accounting methods used The bank must disclose the fair value of both hedge stake and hedge funds.